Poor energy ratings when appliances convey? - Corinne Faure; Joachim Schleich (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
Conveyance, i.e., leaving one's appliance in the dwelling when moving out, shortens the expected length of ownership of an appliance and may therefore lead to the purchase of less energy-efficient appliances. Employing a demo-graphically representative survey in Spain, this paper uses statistical-econometric analyses to explore the effects of conveyance on stated adoption of energy-efficient appliances (refrigerators or fridge-freezer combinations, freezers, dishwashers, and washing machines). The findings suggest that the take-up of energy-efficient appliances is on average about 8%-points lower when appliances convey. In addition, conveyance appears to have comparable effects for renters and homeowners. These findings therefore suggest that conveyance contributes to explaining the energy efficiency paradox. Finally, the results appear robust to a series of robustness checks involving alternative assumptions about the distribution and data generating process, the specifications of the dependent variable, and the handling of missing values. They also provide insights for policy-making.
urn:nbn:de:0011-n-5744513
Keywords: 330; energy efficiency; conveyance; appliances; adoption; energy efficiency paradox; econometrics